STUDI PERBEDAAN MODEL PROJECT BASED LEARNING BERBASIS PROYEK MATH ON THE STREET DAN PEMBELAJARAN LANGSUNG PADA HASIL BELAJAR MATEMATIKA SISWA MATERI PERBANDINGAN - Walean, Virgina Vreisy; Regar, Vivian Eleonara; Pulukadang, Rosiah Juliati (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
This study aims to compare students’ learning outcomes on ratio material through two different models, namely the Project Based Learning model and Direct Instruction. The research was conducted at SMP Negeri 1 Modoinding using a quasi-experimental design with a Pretest Posttest control group model. The PjBL class as the experimental group followed project-based learning involving field observation activities, while the Direct Instruction class as the control group received learning through teacher explanations and practice exercises. The research instrument was a learning outcomes test administered before and after the treatment. The data were analyzed through normality testing, homogeneity testing, and a t-test to determine whether there was a significant difference between the two classes. The results showed that the mean Posttest score of the experimental class (83.72) was significantly higher than the control class (76.08), with t-value = 3.958 > t-table = 2.011 (α = 0.05). Students who were involved in field projects appeared to better understand the concept of ratios because they processed the data they collected themselves, so that the learning process felt closer to real-life situations. These findings indicate that the implementation of PjBL based on the Math On The Street project has a positive effect on students’ learning outcomes, especially on ratio material, and can be an alternative form of learning that is more meaningful compared to the Direct Instruction model